GENETIC DIVERSITY OF Pyricularia grisea, THE CAUSAL AGENT OF RICE BLAST BY SRR - Mohammad Reza Safari Motlagh; Fatemeh Hbibi; Ali Akbar Ebadi (Acta Scientiarum Polonorum: Hortorum Cultus, 2015)
Pyricularia grisea, the rice blast fungus is the main pathological threats to rice crop in Iran and worldwide. In this research was evaluated the genetic diversity of P. grisea collected from different fields of Guilan province by using of 14 microsatellite primers. These primers produced 64 polymorphic bands by an average of 4.57 bands for each marker. An average of polymorphic information content in whole primers was 0.734, an average of effective number of alleles was 2.68, an average of Nei’s expected heterozygosity was 0.734 and an average of Shannon’s information index was 1.05. Primer SSR43,44 had the most polymorphic information content (PIC = 0.85), observed number of alleles (na = 8), effective number of alleles (ne = 3.76), Nei’s expected heterozygosity (Ne = 0.861) and Shannon’s information index (I = 1.38). This marker was the best primer between 14 used primers for evaluation the genetic diversity of P. grisea. Cluster analysis was done with simple matching similarity matrix and UPGMA method. The results showed that the studied isolates were classified into 3 lineages by cutting off the dendrogram at 0.76 similar linkage level. Number 1 was the major group and represented most of those isolates. Results of principal coordinate analysis also divided the isolates into three groups exactly similar to obtained with cluster analysis. Overall, our results confirmed that microsatellite primers were good and suitable markers for analyzing structure of P. grisea.